Cell‐Instructive Microgels with Tailor‐Made Physicochemical Properties. Issue 42 (9th September 2015) - Allazetta, Simone; Kolb, Laura; Zerbib, Samantha; Bardy, Jo'an; Lutolf, Matthias P.
Abstract : A microfluidic in vitro cell encapsulation platform to systematically test the effects of microenvironmental parameters on cell fate in 3D is developed. Multiple cell types including fibroblasts, embryonic stem cells, and cancer cells are incorporated in enzymatically cross‐linked poly(ethylene glycol)‐based microgels having defined and tunable mechanical and biochemical properties. Furthermore, different approaches to prevent cell "escape" from the microcapsules are explored and shown to substantially enhance the potential of this technology. Finally, coencapsulation of microgels within nondegradable gels allows cell viability, proliferation, and morphology to be studied in different microenvironmental conditions up to two weeks in culture. Abstract : A microfluidic in vitro cell encapsulation platform to systematically test the effects of microenvironmental parameters on cell fate in 3D is developed. Multiple mammalian cell types are incorporated in enzymatically cross‐linked poly(ethylene glycol)‐based microgels with defined and tunable mechanical and biochemical properties.